Pulp Canal Obliteration Following Traumatic Dental Injury in an Upper Lateral Incisor: A Case Report with 3-year Follow-up: Pulp canal obliteration - da Cunha Isaltino, Marina; de Sousa , Wesley Viana; Souto Montenegro , Luiza de Almeida; Velozo Telles, Christianne Tavares; Figueredo Cassimiro da Silva , Marcely Cristiny; de Albuquerque, Diana Santana (Iranian Endodontic Journal, 2024)
Endodontic management of teeth afflicted with pulp canal obliteration faces a challenge due to the heightened risk of complications including excessive wear, perforation, and suboptimal chemomechanical preparation. This report aims to elucidate the clinical endodontic strategy employed in addressing pulp canal obliteration after a history of dental trauma and an associated periradicular lesion in an upper lateral incisor. A patient visited the dental emergency department with symptoms of apical swelling, acute persistent pain, and discoloration of tooth 22. Following comprehensive clinical evaluation and cone-beam computed tomography, the diagnosis of pulp canal obliteration involving the cervical and middle thirds of the tooth, alongside an acute periradicular abscess was established. Root canal was accessed using tomographic image planning, augmented by loupe magnification and ultrasonic instrumentation. Precise identification of the access cavity was radiographically confirmed, preceded by thorough irrigation with 2.5% sodium hypochlorite and subsequent cervical and middle third preparation. Verification of the working length by an electronic apex locator ensured precise apical preparation, followed by passive ultrasonic irrigation to optimize disinfection and to enhance penetrability of intracanal calcium hydroxide medication, administered for 15 days to eliminate microbial invasion. Upon resolution of symptoms, root canal obturation employing thermo-mechanical compaction and coronal sealing with composite resin was accomplished. Radiographic assessment after a one-year interval presented evidence of lesion regression and bone repair. Subsequent cone-beam computed tomography imaging at the three-year follow-up confirmed complete healing of the periradicular tissues, attesting to the efficacy of the endodontic intervention.